Implementation Of The Montessori Practical Life Skills Method To Develop Fine Motor Skills In Children In Group A At The Surya Citra Angkasa Early Childhood Education Center - Susanti, Mira; Muhajirin, Muhammad; Hamdani, Muh. (JUPE : Jurnal Pendidikan Mandala, 2025)
Mira Susanti (2025). This research is entitled implementation of the montessori practical life skills method to develop fine motor skills in children in group a at the surya citra angkasa early childhood education center. The purpose of this study was to determine the development of Fine Motor Skills in Group A Children at Surya Citra Angkasa Preschool. The type of research used was Classroom Action Research with research subjects of group A PAUD child with a total of 10 children. This research was carried out in two cycles and in 1 cycle it was divided into 4 stages, namely planning, implementation, observation and reflection. The results of the pre-cycle research were only 30% completed, in cycle 1 it can be explained that children's fine motor skills developed by 70% and in cycle 2 it increased to 90% of 10 children, there were 2 children who obtained the criteria for developing according to expectations and 7 children obtained the criteria for developing very well and 1 child obtained the criteria for starting to develop. This shows that the application of the Montessori method in developing children's fine motor skills at Surya Citra Angkasa Preschool is very effective in developing children's motor skills. According to the researcher's observations, this method frees children to explore their environment, teaches independence, and various interesting activities such as experiments, demonstrations, and exercises of practical life. This allows children's motor development to progress rapidly, further stimulating and honing their fine motor skills.